A Study of the Effects of Tornado Translation on Wind Loading Using a Potential Flow Model - Huo, Shuan; Wang, Jin; Haan, Fred L.; Kopp, Gregory A.; Sterling, Mark (Frontiers in Built Environment, 2022)
This paper investigates the effects of tornado translation on pressure and overall force experienced by an airfoil subjected to tornado loading and presents a framework to reproduce the flow conditions and effects of a moving tornado. A thin symmetrical airfoil was used to explore the effects of tornado translation on a body. A panel method was used to compute the flow around an airfoil and an idealised tornado is represented using a moving vortex via unsteady potential flow. Analysis showed that the maximum overall pressure at a point was found to increase by up to 20% when the normalised translating velocity was 10% of the tangential velocity, but increases up to 60% when the normalised translating velocity is 30% of the tangential velocity. Investigation on the impact of varying airfoil thickness (Case 2) revealed that the location of the tornado has significant effect on the overall lift force. However, the overall lift force appeared to be largely insensitive to the tornado translation velocity due gross changes in pressure on either side of the airfoil cancelling each other out. Further comparison with varying airfoil sizes and distance to tornado translating path (Case 3) showed that the relative inflow and outflow angle is the primary factor affecting the lift on the airfoil. Additionally, the maximum forces on a body subjected to a moving tornado can be predicted using uniform flow providing that the appropriate range of inflow angles are known. Based on the analysis on the database of National Oceanic and Atmospheric Administration (NOAA), the normalised translation speed of the recorded tornadoes across the EF scales, appears to vary from 0.25 to 0.37, with an average of 0.32 (~18.8m/s). Finally, the framework using uniform flow to reproduce the flow conditions which are comparable to those generated by a translating vortex simulator is proposed and discussed in detail.